Advances in Doxorubicin-based nano-drug delivery system in triple negative breast cancer - Zeng, Weiwei; Luo, Yuning; Gan, Dali; Zhang, Yaofeng; Deng, Huan; Liu, Guohui (Frontiers in Bioengineering and Biotechnology, 2023)
Triple negative breast cancer (TNBC) is one of the most aggressive breast cancer. Due to the unique cell phenotype, aggressiveness, metastatic potential and lack of receptors or targets, chemotherapy is the choice of treatment for TNBC. Doxorubicin (DOX), one of the representative agents of anthracycline chemotherapy, has better efficacy in patients with metastatic TNBC (mTNBC). DOX in anthracycline-based chemotherapy regimens have higher response rates. Nano-drug delivery systems possess unique targeting and ability of co-load, deliver and release chemotherapeutic drugs, active gene fragments and immune enhancing factors to effectively inhibit or kill tumor cells. Therefore, advances in nano-drug delivery systems for DOX therapy have attracted a considerable amount of attention from researchers. In this article, we have reviewed the progress of nano-drug delivery systems (e.g., Nanoparticles, Liposomes, Micelles, Nanogels, Dendrimers, Exosomes, etc.) applied to DOX in the treatment of TNBC. We also summarize the current progress of clinical trials of DOX combined with immune checkpoint inhibitors (ICIS) for the treatment of TNBC. The merits, demerits and future development of nanomedicine delivery systems in the treatment of TNBC are also envisioned, with the aim of providing a new class of safe and efficient thoughts for the treatment of TNBC.